Pengaruh Penggunaan Gadget terhadap Perkembangan Anak Usia Pra Sekolah di Kecamatan Banda Sakti Lhokseumawe - Zikra Ihtasya Annabila; Mauliza Mauliza; Cut Sidrah Nadira (Lembaga Pengembangan Kinerja Dosen, 2025)
Developmental deviations in children under five years of age are estimated to affect approximately 5-10% of this population, with inappropriate stimulation, particularly from electronic devices such as gadgets, being a significant contributing factor. Early exposure to these technologies can lead to decreased physical activity, adversely impacting the overall development of children, including their gross and fine motor skills, language acquisition, socialization, and independence. The objective of this study was to evaluate the effect of gadget usage on the developmental outcomes of preschool children in the Banda Sakti District of Lhokseumawe, utilizing an observational analytic research method with a cross-sectional design to collect both primary and secondary data. The results indicated varying levels of gadget usage among respondents: 40 individuals (42%) fell into the high usage category, 31 individuals (32%) were classified as moderate users, and 25 individuals (26%) were categorized as low users. Among those with low gadget usage, 6 respondents (24%) displayed questionable developmental outcomes, while in the moderate and high usage categories, 22 respondents (71.1%) and 22 respondents (55%) respectively exhibited similar concerns. This study reveals that a significant number of children are facing developmental disorders, with 21 respondents (37.5%) experiencing challenges related to socialization and independence, and 17 respondents (30.4%) demonstrating speech and language difficulties. Notably, a substantial proportion of preschool children (52 respondents or 54.2%) were identified as having high levels of gadget usage, and the study established a significant correlation between the intensity of gadget use and the occurrence of developmental disorders in preschool children within the Banda Sakti District of Lhokseumawe.